Penerapan dan Manfaat Pengunaan Aplikasi Canva untuk Mahasiswa dalam Belajar Bahasa Inggris sebagai Bahasa Kedua (ESL) di Universitas Palembang - Novianty, Melisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT The aim of this research is to find out the benefits of the Canva Application in teaching and learning process in lectures, especially in learning English as a Second Language (ESL) at Palembang University. The research method in this article uses a qualitative method. The technique used is to interview students’ opinions and provide questionnaires. The Sample used was Students from the English Language Education Study Program in the academic year 2024/2025, odd semester. The number of Sample is 16 students. Whereas, the results of this research can be concluded that the Application and benefits of using Canva Application can make it easier for students in the learning process, especially in designing Power Points (PPT) and Posters with attractive colors, thereby making students enthusiastic about leaning. Therefore, the Canva Application can be recommended for use in the learning process.